MEMBACA MASYARAKAT ACEH MELALUI PUJIAN DALAM SYAIR TARIAN RAPA’I - Cut Irna Liyana (Jurnal Community, 2018)
Abstract The use of language in a society can reflect the culture of one society. The aim of this study is to describe the Acehnese culture and perspective about compliment throught Syair of Rapa’I Dance. This is a qualitative research. Compliments in Syair of Rapa’I Dance are data in this research. To collect the data, researcher do observation and to analyze the data, interpretative method is used. The result shows that, compliment on Rapa'I's dance shows that in the Rapa'I Aceh, compliment is generally addressed to God. This is because the Acehnese culture that puts forward the values of Islam so that compliment as praise that exists is only aimed at God.  Key words: compliment, language, society